Contemporary Issues in Marketing and Consumer Behaviour - Parsons, Elizabeth; Maclaran, Pauline; Ashman, Rachel; Chatzidakis, Andreas (London Routledge, 2023)
This third edition of Contemporary Issues in Marketing and Consumer Behaviour has been revised and updated to reflect the fast-changing world we live in. The new state of the art chapter on digital marketing digs deeply into two new frontiers of marketing which have significant impact on contemporary social life: influencer marketing, and online gaming. Other new topics help us to understand how marketing can perpetuate local and global inequality through creating and sustaining hierarchies of knowledge and influencing norms of race, disability, gender and sexual orientation.
Keywords: Digital Marketing; Marketing management; Consumer behaviour